Governance for well-being: fostering meaningful and mindful living in political philosophy - Mehmet Recai Uygur; Bahman Peyravi (Entrepreneurship and Sustainability Issues)
This research investigates philosophical and mindful visions of political governance, sustainable development, and well-being. It explores how nations and their policies can enhance individual and community well-being while remaining sociologically, environmentally, and economically sustainable. Using case studies of Bhutan's Gross National Happiness (GNH) and Scandinavian welfare states, the paper demonstrates governance models prioritising social justice, environmental protection, and economic goals. The study integrates the philosophical ideas of Amartya Sen, who emphasises the expansion of individual capabilities; John Rawls, who advocates for justice as fairness; and Michel Foucault, who critiques power structures that shape societal norms. The research builds on existing frameworks linking sustainable development and governance, offering recommendations for orienting governance toward equity, justice, and ethical responsibility.